Study on the knowledge, attitude and practice of contraception in Kerala, centered around a tertiary care centre - K. K., Akshay Kumar; Chandran, Jyoti R.; S., Sreelakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Family planning is a public health cornerstone. In Kerala, India, despite high literacy, contraceptive use is dominated by female sterilization, with low uptake of spacing methods and minimal male participation. This suggests significant gaps in knowledge and attitudes. This study aimed to assess the awareness, specific knowledge and attitudes towards contraceptive methods in a mixed population of Kerala. Methods: A cross-sectional, questionnaire-based study was conducted from May 2024 to September 2025 among 500 individuals (84.2% female; 48% healthcare workers) residing in Kerala, aged above 18 years. The sample size was justified using a 71.6% anticipated prevalence from a parent study. Data was collected via an online survey distributed at a tertiary maternity hospital and the wider community. Main outcome measures were awareness levels, specific knowledge, lifetime usage and attitudes towards intrauterine devices (IUDs) and male sterilization, analyzed using t-tests and Chi-Square tests. Results: General awareness of contraception was nearly universal, but lifetime usage was low (22.8%). A significant knowledge-practice gap was identified. Participants who had used contraception had significantly higher mean awareness scores (7.35) than non-users (6.22) (t=3.90, p<0.001). Healthcare workers (Mean Score: 7.67) were significantly more knowledgeable than non-healthcare workers (Mean Score: 5.37) (t=10.19, p<0.001), but this did not correlate with higher personal use (p=0.492). Education level was highly associated with willingness to accept an IUD (p<0.001), but economic status was not associated with contraceptive use (p=0.373). Conclusions: Despite high general awareness, significant gaps in detailed knowledge and low practical adoption persist. Misconceptions and reluctance, particularly towards male sterilization and long-acting reversible contraceptives (LARC), are prevalent. Targeted educational interventions addressing specific procedural fears-and specifically sensitizing healthcare providers to their own biases-are necessary to bridge this knowledge-practice gap.